Language Policy and Communication Policy - Same Same but Different? - Bergenholtz, Henning; Johnsen, Mia (HERMES - Journal of Language and Communication in Business, 2006)
Surprisingly, no attempts have yet been made to relate language policy and communication policy. This is the case in theoretical contributions on language policy and theoretical contributions on communication policy alike, none of which mentions the other concept. It is also the case in existing language policies where the term communication policy is not referred to at all. Likewise, the term language policy is not found in communication policies, even when a particular company or organisation has a language policy as well as a communication policy. This contribution aims to deﬁne both terms and subsequently to establish the relation between them.